Small cell lung cancer in never-smokers. Issue 3 (23rd December 2015) - Torres-Durán, María; Ruano-Ravina, Alberto; Kelsey, Karl T.; Parente-Lamelas, Isaura; Provencio, Mariano; Leiro-Fernández, Virginia; Abal-Arca, José; Montero-Martínez, Carmen; Vidal-Garcia, Iria; Pena, Carolina; Castro-Añón, Olalla; Golpe-Gómez, Antonio; et al.
Our aim was to describe the characteristics of a case-series of never-smoker small cell lung cancer (SCLC) cases. Cases of SCLC were selected from a prospective, multicenter, hospital-based case–control study performed in Spain. Participants were never-smokers older than 30 years with an anatomo-pathological confirmation of primary lung cancer. We collected clinical and epidemiological variables according to the study's protocol. We included 19 SCLC cases, 18 females (94.7%), median age 75 years (interquartile range (IQR) 70–80 years). Median residential radon concentration was 195 Bq·m −3 (IQR 130–229 Bq·m −3 ). 10 patients had limited disease and nine had extended disease. Median survival was 242 days (IQR 94–496 days); 1- and 2-year survival were 36.8% and 17.6%, respectively. Survival was much higher for individuals with limited disease than for those with extended disease (median 336 versus 235 days; 1-year survival 50% versus 22.2% and 2-year survival 27% versus 0%, respectively). Performance status at diagnosis was closely related to survival. SCLC is an infrequent, highly aggressive disease in never-smokers. Survival is poor, even for limited disease. Age at diagnosis in SCLC is higher than that observed for never-smokers with adenocarcinoma. Residential radon exposure is higher than the action levels recommended by the World Health Organization. Small cell lung cancer in never-smokers has a poor survival and is diagnosed at older ages than other lung cancers http://ow.ly/USS2W